Music and sedation relieve intraoperative stress: A randomized controlled trial. - Kaoru Yamashita; Toshiro Kibe; Akari Uto; Shusei Yoshimine; Minako Uchino; Mitsutaka Sugimura (PLoS ONE)
Trial registration UMIN Clinical Trials Registry, UMIN 000054970.